REFORMULASI PENGISIAN JABATAN ANGGOTA DEWAN PERWAKILAN RAKYAT DAERAH MELALUI PEMILIHAN SERENTAK LOKAL - Tauda, Gunawan A. (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2021)
The 2019 concurrent elections became the biggest history of Indonesia's democracy. However, the simultaneous election provisions stipulated in Election Law have complexity, and at the same time have a heavy technical implementation impact for the organizers and voters. On the other hand, the meaning of the Regional House of Representatives (DPRD) as an element of regional government administration through the Regional Government Law opens conceptual space to initiate alternative patterns of filling their positions through regional simultaneous electoral mechanisms. This alternative pattern is intended to reformulate the mechanism for the implementation of general elections for DPRD members, which were previously held simultaneously in national elections, then carried out congruently on the same day as the regional elections. This can be implemented through changes to the Election Law, without having to change the 1945 Constitution. Substantially, the amendment is limited to the time aspect of elections for DPRD members.